Adsorption of glycerol, monoglycerides and diglycerides present in biodiesel produced from soybean oil - Vasques, Erika de Castro (Environmental technology, 2013)
The most common methods currently used for the removal of waste glycerol, monoglycerides and diglycerides remaining after phase separation during biodiesel production involve wet processes. These procedures are not environmentally viable because they require large volumes of water and thus generate significant quantities of effluent. In this study, adsorption was employed to replace this purification step. Some commercial activated carbons were tested along with adsorbents chemically modified with HNO3. A kinetics study was conducted at 30 degrees C and adsorption isotherms were obtained at 20 degrees C, 30 degrees C and 40 degrees C. The results indicated that the adsorption of glycerol increased with the use of chemically-modified activated carbon, showing that pH has a strong influence on glycerol adsorption. The pseudo-first-order kinetic model provided the best fit with the experimental data for the monoglycerides while the pseudo-second-order model showed a better fit for the glycerol and diglycerides. The Freundlich model had the best fit with experimental data on the adsorption equilibrium for all temperatures. The thermodynamic study indicated that the adsorption process is endothermic and thus adsorption is favoured by increasing the temperature. The adsorption process using chemically-modified activated carbon was therefore very effective for the removal of waste glycerol resulting from biodiesel production, which is of considerable significance given the legal limits imposed